Does Multiparametric Magnetic Resonance of Prostate Outperform Risk Calculators in Predicting Prostate Cancer in Biopsy Naïve Patients? - Falagario, Ugo Giovanni; Silecchia, Giovanni; Bruno, Salvatore Mariano; Di Nauta, Michele; Auciello, Mario; Sanguedolce, Francesca; Milillo, Paola; Macarini, Luca; Selvaggio, Oscar; Carrieri, Giuseppe; Cormio, Luigi (Frontiers in Oncology, 2021)
Background: EAU guidelines recommend using risk-calculators (RC), imaging or additional biomarkers in asymptomatic men at risk of Prostate cancer (PCa). Objectives: to compare the performance of mpMRI, a RC we recently developed, and two commonly used RC not including mpMRI in predicting the risk of PCa, as well as the added value of mpMRI to each RC. Design, Setting, and Participants: Single-center retrospective study evaluating 221 biopsy-naïve patients who underwent prebiopsy mpMRI. Outcome Measurements and Statistical Analysis: Patients’ probabilities of any PCa and clinically significant PCa (csPC, defined as Gleason-Score ≥3+4) were computed according to mpMRI, European Randomized Study of Screening for Prostate Cancer RC (ERSPC-RC), the Prostate Biopsy Collaborative Group RC (PBCG-RC) and the Foggia Prostate Cancer RC (FPC-RC). Logistic regression, AUC and Decision curve analysis (DCA) were used to assess the accuracy of tested models. Results and Limitation: The FPC-RC outperformed mpMRI in diagnosing both any PCa (AUC 0.76 vs 0.69) and csPCa (AUC 0.80 vs 0.75). Conversely mpMRI showed an higher accuracy in predicting any PCa compared the PBCG-RC and the ERSPC-RC but similar performances in predicting csPCa. At multivariable analysis predicting csPCa and any PCa, the addition of mpMRI findings improved the accuracy of each calculator. DCA showed that the FPC-RC provided a greater net benefit than mpMRI and the other RC’s. The addition of mpMRI findings improved the net benefit provided by each calculator. Conclusions: mpMRI was outperformed by the novel FPC-RC and showed similar performances compared to the PBCG and ERSPC RC’s in predicting csPCa. The addition of mpMRI findings improved the diagnostic accuracy of each of these calculators